Muslim reformist action in nineteenth-century Tunisia - El-Mesawi, Mohamed El-Tahir (Association of Muslim Social Scientists & The International Institute of Islamic Thought, 2008)
This article revisits the origins of the Islamic reformist movement that arose in the nieneteenth century. Tunisia was chosen because the spirit of reform manifested itself in the form of intellectual activity and socio-political action. The article highlights the features of the Tunisian experience before the French occupation in 1881, reveals the cooperation and complementary relationship between religious scholars and statesmen that gave the reform efforts their substance and form, and discusses the dynamic of the forces that were in play and helped determine the attempted reforms' fate.